2018
DOI: 10.1177/0020720918791422
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous machine analysis and modelling in LabVIEW: An educational tool for transient stability studies

Abstract: A three-phase synchronous machine was, and still is, one of the most important element in today’s power generation systems (operating as a generator) or in distribution–load systems (operating as a motor). Thus, a suitable and detailed model is required to be used by students and future engineers in order to deal with transient stability analyses. For this purpose, the paper presents and analyses a procedure by which the mathematical modelling of a three-phase, four-pole, synchronous machine can be implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…For example, label the packaging box of variable data (image, barcode or security function), which is related to innovative solutions to stimulate brand vitality. 17 Third, higher productivity can help digital printing get more orders. In the future, there will be more 3-10km printing capacity labels and 3-7km printing capacity flexible packaging from traditional printing to digital printing.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…For example, label the packaging box of variable data (image, barcode or security function), which is related to innovative solutions to stimulate brand vitality. 17 Third, higher productivity can help digital printing get more orders. In the future, there will be more 3-10km printing capacity labels and 3-7km printing capacity flexible packaging from traditional printing to digital printing.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Ao utilizá-la eles puderam reforçar não apenas o conhecimento teórico sobre o conteúdo abordado, mas também vivenciar a ocultação de uma mensagem em uma imagem. Exemplos do uso de ferramentas computacionais para auxiliar estudantes na melhor compreensão dos mais diversos conteúdos podem ser vistos em (Karnavas e Lygouras, 2018;Biasi et al, 2019;Feijó et al, 2019;Panegalli et al, 2019).…”
Section: Ferramenta Desenvolvidaunclassified
“…The comparison between on-site laboratories and virtual laboratories has been clarified. Karnavas et al 4 presented stability studies of synchronous machines in the LABVIEW environment and the simulation results showed the effectiveness of the proposed educational tool for modeling synchronous machines and teaching undergraduate students. Other alternative tools can be found in Oliveira et al, 5 Omer et al 6 and Gu¨ney et al, 7 with emphasis on different issues in energy engineering education.…”
Section: Introductionmentioning
confidence: 99%